The Design Karo Cultural Centre with Neo-Vernacular Architecture Approach - Wahyuni Zahrah; Muhammad Yusuf Rahmadani (International Journal of Architecture and Urbanism, 2019)
Culture in North Sumatra is a very scant appreciation from the public. In particular, the community's enthusiastic Karo Ground against art objects tend to be low and continues to decline; it is also affected by the impact of the modernization of Western culture. It is required for a container or a place that is used to introduce, studying, preserving culture Karo, addressed to the community, domestic and foreign, the purpose is to make many parties better understand or know about the culture that exists in the land of Karo. Neo vernacular Karo was chosen as the theme of the design so as not to eliminate the side of culture Karo as well as local wisdom applied physical and nonphysical. The theme is used in the concept of building mass Si Walu Jabu into the project by taking the basic shapes in Karo, as well as custom homes, apply flexibility in floor plan traditional house Karo on every space in the cultural center. Design of area designated as Tahura with consideration of its strategic footprint and also as the gateway tour in the land of Karo. Expected with the existence of this cultural center, domestic and foreign, and especially the community can engage in its own agenda in the preservation, experience, recognition, and can enjoy Karo culture itself comfortably.